Having the second leg at home - Advantage in the UEFA Champions League knockout phase? - Eugster, M. J. A.; Gertheiss, J.; Kaiser, S. (Journal of Quantitative Analysis in Sports, 2011)
In soccer knockout ties, which are played in a two-legged format, the team having the return match at home is usually seen as advantaged. For checking this common belief, we analyzed matches of the UEFA Champions League knockout phase since 1994/1995. It is shown that the observed differences in frequencies of winning between teams first playing away and those which are first playing at home can be completely explained by their performances on the group stage and—more importantly—by the teams' general strength.